Non-Litigation Mechanisms for Resolving Deviant Religious Sect Cases in Aceh: A Sociology of Law Analysis of the Role of the Aceh Ulama Consultative Council - Muzakkir Zakaria; Siti Zubaidah Ismail (Fakultas Syariah IAIN Langsa, 2026)
The enforcement of aqidah law in Aceh, from a normative perspective, should ideally be carried out through formal legal mechanisms that ensure legal certainty, accountability, and the protection of freedom of religion in accordance with the principles of the rule of law and the provisions of Qanun Number 8 of 2015 concerning the Development and Protection of Aqidah. Empirical reality demonstrates that the resolution of deviant sect cases is predominantly conducted through non-litigation mechanisms by the Aceh Ulama Consultative Assembly (Majelis Permusyawaratan Ulama/MPU) through fatwas, religious guidance, dialogue, and persuasive religious approaches. This condition reflects a clear gap between das sollen and das sein in the enforcement of aqidah law in Aceh. This study aims to analyze the settlement of deviant sect cases from the perspective of the sociology of law by focusing on the role of the MPU and the social implications arising from the dominance of non-litigation mechanisms. The research employs an empirical legal method with a sociology of law approach through statutory analysis, document analysis, and in-depth interviews with religious leaders and relevant institutional actors. The findings indicate that non-litigation settlement mechanisms are effective in reducing horizontal conflicts, maintaining social stability, and fostering legal compliance based on the legitimacy of ulama and the tradition of deliberative culture within Acehnese society. The dominance of non-litigation mechanisms also has the potential to weaken legal certainty, accountability, and the protection of religious rights if it is not balanced by proportional litigation mechanisms. A balanced integration between religious approaches and formal legal processes constitutes an urgent necessity in the enforcement of aqidah law in Aceh in order to achieve justice that is effective, constitutional, and sustainable.